O monumento pré‑histórico da Praia das Maçãs: leitura comparada dos dados da escavação arqueológica realizada em 1961 e das intervenções arqueológicas de 2020‑2022: DOI: https://doi.org/10.5281/zenodo.10402490 - Costeira, Catarina; Porfírio, Eduardo; Cardoso, João Luís; Costa, Ana Maria; Simões, Teresa (Estudos Arqueológicos de Oeiras, 2023)
A comparative study is presented of the results of the excavation of the prehistoric monument of Praia das Maçãs obtained in 1961, based on the existing documentation kept in archives and that which has since been published, with those obtained in the archaeological intervention carried between 2020 and 2022. The study carried out resulted in several new conclusions that allowed us to characterize with greater rigor the sequence adopted in the construction of this complex burial monument, which is also of notable importance from the perspective of its recovery and consolidation, with a view to its public enjoyment.